2005
DOI: 10.1677/jme.1.01720
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced impairment in insulin secretion is associated with reduction in islet glucokinase in a mouse model of susceptibility to islet dysfunction

Abstract: Type 2 diabetes is characterized by islet dysfunction resulting in hyperglycemia, which can then lead to further deterioration in islet function. A possible mechanism for hyperglycemia-induced islet dysfunction is the accumulation of advanced glycation end products (AGE). The DBA/2 mouse develops pancreatic islet dysfunction when exposed to a high glucose environment and/or obesity-induced insulin resistance. To determine the biochemical cause of dysfunction, DBA/2 and C57BL/6 control islets were incubated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 49 publications
7
33
0
2
Order By: Relevance
“…[16][17][18][19][20][21][22] Basal insulin release at 5.6 mM glucose was not affected by hyperglycemia but the secretory response to 16.7 mM glucose was impaired by 48 and 72 h exposure to 25 mM glucose. We also observed that insulin release from 1.1B4 cells chronically exposed to hyperglycemia for 48 and 72 h was significantly reduced in response to alanine, GLP-1, KCl, elevated Ca 2+ , or forskolin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] Basal insulin release at 5.6 mM glucose was not affected by hyperglycemia but the secretory response to 16.7 mM glucose was impaired by 48 and 72 h exposure to 25 mM glucose. We also observed that insulin release from 1.1B4 cells chronically exposed to hyperglycemia for 48 and 72 h was significantly reduced in response to alanine, GLP-1, KCl, elevated Ca 2+ , or forskolin.…”
Section: Discussionmentioning
confidence: 97%
“…29 This is supported by observations in INS-1E cells exposed to hyperglycemia and isolated human islets. 19,[30][31][32][33][34] Such downregulation could be due to concomitant reduction in PDX1, which is involved in regulation of insulin gene transcription and expression of other important genes involved in β-cell secretory function. 16 Reduced PDX1 levels have been observed also in HIT-T15 cells, INS-1E cells and human islets treated with high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed to determine protein expression levels of SUR1 and Kir6.2 in the pellet fraction of homogenised pancreata as previously described (Kooptiwut et al 2005). Protein was loaded onto a 10% resolving gel (Kir6.2) or a 7.5% resolving gel (SUR1) and immunodetected using their respective specific primary antibodies from Santa Cruz Biotechnology, Inc. at a 1:500 dilution overnight at 4 8C; anti-Kir6.2 (H-55) (sc-20809) and anti-SUR1 (C-16) (sc-5789) antibodies respectively.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Islets were isolated and incubated for insulin secretion studies as previously described (Kooptiwut et al 2005, Zraika, et al 2006. Islets were prepared for cDNA synthesis and subsequent mRNA analysis using the method as previously described (Aston-Mourney et al 2007).…”
Section: Islet Isolation and Cdna Preparationmentioning
confidence: 99%
“…We have recently completed a 7-year study on the DBA/2 mouse, a strain that is susceptible to beta cell failure and diabetes when genetically stressed with obesity [15] or exposed to a high-glucose environment [16,17]. We found that in contrast to C57BL/6 mice, which have a genetic disruption in Nnt, and the 129T2 mice, which show low levels of expression, the diabetes-susceptible DBA/2 mice show a fivefold overexpression of this gene, which encodes the mitochondrial proton pump known as nicotinamide nucleotide transhydrogenase.…”
Section: Ermentioning
confidence: 99%